Contribution of russian scientists and specialists to the development of the oil and gas industry in the Caspian region - Yu. Р. Panov; U. S. Serikova; V. Sh. Gurbanov (Известия высших учебных заведений: Геология и разведка)
Russian scientists, engineers, inventors, and talented entrepreneurs have made a great contribution to the development the Caspian region, one of the main sources of hydrocarbons in the world. In many respects, these specialists have determined the directions of rational development of the oil industry in coastal states and the oil business as a whole. Russian scientists have played an important role in the formation of national scientific schools, which have had a significant impact on the global knowledge in the field. This article memorializes the names of scientists and prominent specialists who have contributed to the development of the oil and gas industry, setting the example of service to the Motherland, Society, and Science. The article is based on the results of a report at the plenary section of the international scientific conference entitled “Formation and development of the oil and gas industry — the contribution of Russian and Azerbaijani scientists and specialists”.